JISMONIY MASHQLARGA O`RGATISHNING ASOSLARI - Kholova Shakhnoza Mardonovna; Musaeva Ma'mura (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
The article analyzes effective methods of teaching physical technique. The main didactic measures taken in the process of gradually teaching children to see and develop their skills, the methodology of the exercises depending on the type and content of the exercises are highlighted. Methods such as partial demonstration of movement, repetition, assistance in recovery and independent maintenance are revealed. The article emphasizes that teaching physical exercises takes into account age-specific physiological and medical support, and methodological recommendations for educators and trainers are given.